2009
DOI: 10.1186/1476-069x-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to outdoor air pollution and diagnosed cardiovascular disease: meta-analysis of three large cross-sectional surveys

Abstract: BackgroundHigher exposure to outdoor air pollution is associated with increased cardiopulmonary deaths, but there is limited evidence about the association between outdoor air pollution and diagnosed cardiovascular disease. Our study aimed to estimate the size of the association between long term exposure to outdoor air pollution and prevalent cardiovascular disease.MethodsWe carried out a cross-sectional analysis of data on more than 19,000 white adults aged 45 and older who participated in three representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Long-term epidemiological studies have indicated a positive association between exposure to high levels of atmospheric PM and severe health effects in subjects with circulatory disturbances (Forbes et al, 2009). The lack of comprehension of this problem has stimulated the development of experimental and epidemiological researches through analytical chemistry, histological and biochemical evaluations (Calderon-Garciduenas et al, 2011;Morgan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term epidemiological studies have indicated a positive association between exposure to high levels of atmospheric PM and severe health effects in subjects with circulatory disturbances (Forbes et al, 2009). The lack of comprehension of this problem has stimulated the development of experimental and epidemiological researches through analytical chemistry, histological and biochemical evaluations (Calderon-Garciduenas et al, 2011;Morgan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that exposure to fine particulate air pollution can lead to various adverse health effects in humans. The most serious health effects have been associated with combustion-and traffic-generated particles in the outdoor air [15,[43][44][45][46]. Indoor PM has also been associated with increased respiratory symptoms [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…A large body of literature detailing the impact of urban environmental stressors on public health [4,9–11]. Urban exposure to noise, air pollution and pesticides are known to increase the likelihood of specific chronic diseases [9–14].…”
Section: Introductionmentioning
confidence: 99%